Land Classification for Optimal Use of Land by Remote Sensing and GIS Technology - Haque, MF; Ali, MS; Haq, MA; Akhand, MMR (Journal of Environmental Science and Natural Resources, 2012)
In this paper, attempt has been made to prepare landuse map for the district of Brahmanbaria, situated in the east-central part of Bangladesh using remote sensing technique. The multi-spectral Landsat TM data for 3 November 2002, 15 December 2004, 01 February 2002, 14 March 2003 and some aerial photographs of December 2000 have been used for land-use mapping for major three crops namely aman rice (late July - early November), winter (rabi) crops and winter (boro) rice. The imagery covers the growing seasons of the above crops, where multi-spectral and multi-temporal signatures for the green vegetations have been shown in spatial domain. The interpretation of the aerial photographs have also been performed and prepared GIS layers containing the water bodies and settlements. All the signature files including the interpretations of aerial photographs have been combined to produce a composite file in GIS layers. These layers were then combined to prepare the landuse maps including the three major crops cultivated round the year. Moreover, the landuse map of Akhaura upazila was compared with the land-type map and a relation of the landuse with the land-type has also been derived. The extracted feature files corresponding to spectral signatures have been overlaid to estimate the distribution of three major crop types in the study area. The result implies that all the three major crops like, aman, rabi and boro were cultivated in the same land which was 9.2% of total land area. Similarly, areas under double and single crops were also estimated and the result revealed that all the three crop types cover 68.3% of the total land area of Brahmanbaria district. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11587 J. Environ. Sci. & Natural Resources, 5(1): 229-237, 2012